STUDI TINGKAT KERUSAKAN VEGETASI MANGROVE DI PERKAMPUNGAN DAPUR ARANG KAMPUNG BAGAN TANJUNG PIAYU KOTA BATAM (The Study of Mangrove Vegetation Damage at Kampung Bagan in Tanjung Piayu Kota Batam) - Efendi, Yarsi (Universitas Riau Kepulauan, 2013)
Mangrove forest in the township of mangrove charcoal Kampung Bagan, Tanjung Piayu Batam, on the condition quantity and quality degradation . The existence of these ecosystems are increasingly threatened by the presence of a variety of human activities especially trees cutting to be burn to made charcoal . The purpose of this study to aim the level of destruction of mangrove ecosystems based on standard criteria and guidelines for the determination of damage to mangroves on the terms of the Decree of the Minister of Environment of the Republic of Indonesia No. . 201/ 2004 . Field survey methods used to identify mangrove vegetation with using transects technique with a square plot , placed on 2 station. Station 1 Sungai Bongkok dan Station2 Teraling Island. We also use questioner to get some information from this communities. Selected respomden are consisting of persons who’s activities on mangrove charcoal conventional industry . Data analysis was performed using the method of vegetation analysis ( density , dominance , frequency , and the index of Important value ) . Composition of vegetation formations in the study site consists of several species , namely: Avicennia marina , Rhizophora stylosa , Rhizophora apiculata , Avicennia officinalis , Lumnitzera littorea , Ceriops decandra , Bruguera gymnorrhioza , Xylocarpus granatum and Hibiscus tiliaceus . The higher of Indeks Important Value is Rhizophora apiculata on every growth level. Density of trees per hectare in the study site consisting of two stations are 107 trees per hectare in Sungai Bongkok station , and 540 trees in Teraling Island.